PERAN ORANG TUA DALAM MEMBINA AKHLAK REMAJA (Studi di Kelurahan Air Duku, Rejang Lebong-Bengkulu) - Tria Masrofah; Fakhruddin Fakhruddin; Mutia Mutia (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2020)
In the concept of Islam, parents play an important role in the implementation of their children’s religious education, and parents must even be able to be role models for their children. For that reason, who became the subjects of this study were the parents in Air Duku village; concerning how was their role in fostering adolescents through education in the family. This study used a qualitative approach, and the data were analyzed using the approach of Miles et al. This study found a conclusion that the parents’ role was quite maximal in educating and instilling the values of Islamic education to foster adolescents’ morals in Air Duku village. The implementation pattern of such a fostering effort is through the inculcation of religious values, guiding, supervising children/adolescents’ behavior, and reprimanding them when doing bad things with the methods of habituation and giving advice, for example, and attention.Keywords: Parents’ Role, Morals, Teenagers